ANALISIS PENETAPAN PERATURAN DAERAH NOMOR 18 TAHUN 2017 TENTANG APBD KABUPATEN SINJAI TAHUN ANGGARAN 2018 - Muhammad Suyuti (Al Qisthi Jurnal Sosial dan Politik, 2019)
This research aims to determine the interaction of actors Sinjai District in the discussion and determination of the Budget District Sinjai Fiscal year 2018. Thisreseach is also aimed to know the process of discussion of draft of regulation about APBD of SinjaiRegency 2018 based on regulation of Minister of Home Affairs No. 33 year 2017 about Guidance ofBudget formation of fiscal year 2018.This research was counducted in DPRD of Sinjai Regency with research base used in this research isqualitative research by using descriptive research type. This research illustrates in depth the interactionbetween DPRD members and the Regional Goverment of Sinjai District along with their staffs in theprocess of discussion and determination of the Sinjai District Budget for Fiscal Year 2018. Researchdata obstained from the members of the Regional House of Sinjai, Chairman of The Commission ofDPRD Sinjai and leaders of the Organization of Regional Devices. The results of the research indicatethat the process of deliberation on the draft of Regional Regulation concerning APBD of Sinjai Regencyis inconsistent with the regulation of the Minister of Home affairs No. 33 year 2017 Concering Guidelinesfor the Preparation of APBD for Budget year 2018. The agreement between DPRD and Local Govermentof Sinjai Regency toward the draft of Local Regulation Concering APBD of Sinjai Regency Budget Year2018 on November 30, 2018 is in accordance with Regulation of Minister of Home Affairs No.33 year2017 about Guidance of Depreciation of APBD of Fiscal Year 2018.